2012
DOI: 10.1089/neu.2011.2144
|View full text |Cite
|
Sign up to set email alerts
|

Social Function in Children and Adolescents after Traumatic Brain Injury: A Systematic Review 1989–2011

Abstract: Clinical reports and case studies suggest that traumatic brain injury (TBI) can have significant social consequences, with social dysfunction reported to be the most debilitating problem for child and adolescent survivors. From a social neuroscience perspective, evidence suggests that social skills are not localized to a specific brain region, but are mediated by an integrated neural network. Many components of this network are susceptible to disruption in the context of TBI. In early development, a brain inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
111
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(123 citation statements)
references
References 71 publications
10
111
0
2
Order By: Relevance
“…However, despite this review identifying seventeen different studies, covering eleven distinct community-based interventions for adolescents following TBI, the quality and applicability of the evidence is limited and highly variable. This finding is consistent with the conclusions of other paediatric TBI rehabilitation systematic reviews and meta-analyses, suggesting limited development of the research area despite repeated calls for higher quality evidence (Rosema, Crowe, & Anderson, 2012;Lindsay et al, 2015;Ross, Dorris, & McMillan, 2011;Laatsch et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…However, despite this review identifying seventeen different studies, covering eleven distinct community-based interventions for adolescents following TBI, the quality and applicability of the evidence is limited and highly variable. This finding is consistent with the conclusions of other paediatric TBI rehabilitation systematic reviews and meta-analyses, suggesting limited development of the research area despite repeated calls for higher quality evidence (Rosema, Crowe, & Anderson, 2012;Lindsay et al, 2015;Ross, Dorris, & McMillan, 2011;Laatsch et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps surprisingly, relative to TD controls children with mild TBI showed reduced pragmatic communication skills at 6-months post-TBI. Although social dysfunction is documented in individuals with moderatesevere TBI (Rosema et al, 2012) we provide evidence that pragmatic language skills may also be vulnerable to the effects of milder generalized injuries.…”
Section: Discussionmentioning
confidence: 71%
“…This is consistent with previous analyses from the full sample from this study using individual measures of theory of mind, 10 as well as research clearly documenting that children with TBI, especially those with more severe injuries, are at risk for such deficits. 6 Children with STBI also demonstrated deficits on several parentrated measures of social adjustment. Children with STBI were reported to have significant overall behavioral symptoms on the BASC-2, as well as problematic social skills and communication on FIG.…”
Section: Discussionmentioning
confidence: 98%
“…5 Disruption of the normal development of SIP as a result of TBI may place children at risk for social isolation, difficulties with peer and family relationships, and decreased quality of life. 6 Although previous research has documented specific deficits in executive function, SIP, and social adjustment after TBI, few studies have addressed the associations among these domains. Dennis and colleagues 7 concluded that early-onset TBI is associated with deficits in multiple regulatory and adaptive skills (i.e., vigilance, selective attention, response manipulation), but did not examine how these predictors interact in accounting for social adjustment.…”
Section: Introductionmentioning
confidence: 99%